Nível de serviço para bicicletas: um estudo de caso nas cidades de São Carlos e Rio Claro - Providelo, Janice Kirner (2011)
This research attempted to study the issue of assessing the level of service for bicycles in Brazilian cities, with the ultimate aim of developing a bicycle level of service model that can be used in medium-sized Brazilian cities. The methodology used for model development began with the identification of attributes that can be used to describe the level of service for bicycles, followed by assessing the perceptions of individuals about the importance of the attributes. Among the methods available to measure the perceptions of individuals about the roadway characteristics related to bicycle transportation, it was chosen to use simulations (video based evaluation). The video was produced through a system in which a portable video camera was attached to the bicycle stern. To compensate for the exclusion of some attributes that could not be assessed through video (such as the sensation of heat, the cost of the bicycle, the health benefits, etc) the simulation method was combined with another method of perception analysis: questionnaires formulated based on the Likert scale. Data collection was performed in a case study in the cities of São Carlos and Rio Claro (São Paulo state), in several educational facilities. In total, 451 questionnaires were administered, 60 in the city of Rio Claro and the rest of them in the city of São Carlos. The results of field study were analyzed through methods of descriptive statistics and correlations, producing the following studies: questionnaires results, classification of participants into types of cyclists, the definition of a scale of acceptability to bicycle use and classification of participants in groups, according to this scale. The Bicycle Level of Service Model was calibrated using the FLOW variable, defined as the volume of motor vehicles divided by the effective width of the road, and the level of service grades resulting from the participants evaluation. The model was validated through cross-validation methodology. The model development resulted in a graphic that can be used to determine the probability of perceived level of service for flow values found on roadways. It was considered that the study reached its primary goal, providing a Bicycle Level of Service Model that can be used in medium-sized Brazilian cities.